Secondary Benefits to Attentional Processing Through Intervention With an Interactive Maths App - Pitchford, Nicola J.; Outhwaite, Laura A. (Frontiers in Psychology, 2019)
Previous research has shown that a specific interactive app, designed to support the development of early mathematical skills and delivered on hand-held tablets, is effective at raising mathematical attainment in young children in low-and high-income countries. In the countries where this app has been deployed, teachers have consistently reported improved concentration skills in children who have received intervention with this app. To investigate the legitimacy of these claims, we conducted secondary data analyses of children’s performance on core cognitive tasks to examine if additional benefits are observed in children who received intervention with the interactive maths app compared to those that did not. We drew on data from a three-arm randomised control trial conducted in a primary school in Malawi (Pitchford, 2015). In addition to assessing mathematical skills, children’s visual attention, short-term memory, and manual processing speed were examined at baseline, before the introduction of the maths app intervention, and at endline, after the intervention had been implemented for 8 weeks. A group of 318 children (73-161 months) attending Standards 1-3 of a Malawian primary school were randomised to receive either the new maths app (treatment group), a non-maths app that required similar interactions to engage with the software as with the maths app (placebo group), or standard teacher-led mathematical practice (control group). Before and after the 8-week intervention period children were assessed on mathematics and core cognitive skills. Results showed the maths app intervention supported significant and independent gains in mathematics and visual attention. Increases in visual attention were attributable only to interactions with the maths app. No significant benefits to attention were found from using the tablet device with non-maths software or standard class-based mathematical practice. These results suggest that high-quality interactive, educational apps can significantly improve attentional processing in addition to the scholastic skills targeted by the intervention.